Outsourcing - Challenges for India - Rangeswara Reddy, J. V. (Prabandhan: Indian Journal of Management, 2010)
Outsourcing involves the transfer of the management and/or day - to - day execution of an entire business function to an external service provider. The client organization and the supplier enter into a contractual agreement that defines the transferred services. Under the agreement, the supplier acquires the means of production in the form of a transfer of people, assets and other resources from the client. The client agrees to procure the services from the supplier for the term of the contract. Business segments typically outsourced include information technology, human resources, facilities, real estate management, and accounting.